2014
DOI: 10.3390/nu6125819
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Supplementation Delays Physical Exhaustion and Prevents Redox Imbalances in Plasma and Soleus Muscles of Wistar Rats

Abstract: Astaxanthin (ASTA) is a pinkish-orange carotenoid commonly found in marine organisms, especially salmon. ASTA is a powerful antioxidant and suggested to provide benefits for human health, including the inhibition of LDL oxidation, UV-photoprotection, and prophylaxis of bacterial stomach ulcers. Exercise is associated to overproduction of free radicals in muscles and plasma, with pivotal participation of iron ions and glutathione (GSH). Thus, ASTA was studied here as an auxiliary supplement to improve antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
5
24
0
Order By: Relevance
“…However, intermittent loading did not prevent capillary regression as well as the previous report (Kanazashi et al 2014). This is likely to be due to overload since exercise associates the overproduction of free radicals in skeletal muscle (Polotow et al 2014).…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…However, intermittent loading did not prevent capillary regression as well as the previous report (Kanazashi et al 2014). This is likely to be due to overload since exercise associates the overproduction of free radicals in skeletal muscle (Polotow et al 2014).…”
Section: Discussionsupporting
confidence: 46%
“…This is likely to be due to overload since exercise associates the overproduction of free radicals in skeletal muscle (Polotow et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Although this depends on the type of exercise and supplementation, animal and human studies have shown benefits of antioxidant supplementation on the recovery of damages caused by exhaustive exercise, either by restoring antioxidant levels or by decreasing the damage. [6][7][8] The α-lipoic acid (ALA) is a disulfide compound with eight carbon atoms which acts as the natural cofactor in the pyruvate dehydrogenase and α-ketoglutarate complexes. 9 The exogenous α-lipoic acid is absorbed and taken to the cells where it is reduced to dihydrolipoic acid (DHLA) which has been shown by presenting potent antioxidant activity.…”
Section: Analysis Of Biomarkers Of Oxidative Stressmentioning
confidence: 99%